2021
DOI: 10.1017/ice.2020.1298
|View full text |Cite
|
Sign up to set email alerts
|

Subglottic suction frequency and adverse ventilator-associated events during critical illness

Abstract: Objective: Tracheal intubation and mechanical ventilation provide essential support for patients with respiratory failure, but the course of mechanical ventilation may be complicated by adverse ventilator-associated events (VAEs), which may or may not be associated with infection. We sought to understand how the frequency of subglottic suction, an indicator of the quantity of sputum produced by ventilated patients, relates to the onset of all VAEs and infection-associated VAEs. Design: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In 2021, a study was conducted to investigate the suctioning frequency and ventilator-related side effects in acutely ill patients. The results of the mentioned research indicated that it is not possible to accurately check the quantity of airway secretions; But by counting the suctioning frequency performed, this amount can be estimated to some extent [33]. It seems that conducting more studies in the future with an intervention duration of more than 48 hours can better show the possible effect of laughter on reducing the number of suctions.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, a study was conducted to investigate the suctioning frequency and ventilator-related side effects in acutely ill patients. The results of the mentioned research indicated that it is not possible to accurately check the quantity of airway secretions; But by counting the suctioning frequency performed, this amount can be estimated to some extent [33]. It seems that conducting more studies in the future with an intervention duration of more than 48 hours can better show the possible effect of laughter on reducing the number of suctions.…”
Section: Discussionmentioning
confidence: 99%
“…Under mechanical ventilation, the patient's ability to spontaneously expectorate is weakened. So, sputum suction becomes an important task of airway management for patients with tracheal intubation or tracheotomy [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this technique carries a risk of causing harm to the tracheal carina, a highly delicate region of the trachea with distinct sharp features. The stimulation caused by the suction tube elicits robust airway responses, resulting in repeated frictional irritation and consequently increasing the likelihood of damage, erosion, and bleeding of the airway mucosa [10]. Consequently, the 2010 guidelines of the American Association for Respiratory Care (AARC) advocate for the utilization of superficial suctioning as opposed to deep suctioning [11].…”
Section: Introductionmentioning
confidence: 99%